Identification of the Critical Point and Critical Control Point for Water Supply System Based on Physical Parameters - Sari, Kartika Rahma; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
At present, attention to the quality of public health is increases. One of the things that highlighted in order to improve the quality of public health is the drinking water aspect. The objects of this research is to implement WHO's new program, entitled Water Safety Plan Program. This program is intended to ensure the quality of drinking water produced appropriate with quality standards and safe for consumption by society, according to health-based targets. Research carried out by measuring and testing the physical parameters of water quality in accordance to Kepmenkes RI nomor 907/MenKes/SK/VII/2002. The measured parameters are temperature, conductivity, and turbidity. Whereas, the tested parameters are Total Dissolved Solid (TDS) and odor. From the results of the measurement and testing, determined the critical point and critical control point of the entire piped water supply system. The critical point is determined from the parameters passed quality standards. By looking at the provision of potable water piping system as a whole, determined which stages that potentially as critical control points. The test results showed that the major critical control point located at the stage of filtration, both for the parameters of turbidity, TDS, or odor, because the next stage of the drinking water supply could not process these parameters again. Critical point in the piped drinking water supply system by Dago Pakar taps located on the parameters of turbidity, with a value that exceeds the quality standard of raw water until the start of the processing stages in the flocculation unit.